Central Hemodynamics and Oxygen Transport during Alveolar Mobilization in Early Periods after Extracorporeal Circulation - I. A. Kozlov; A. A. Romanov; Ye. V. Dzybinskaya (Общая реаниматология)
Objective: to study central hemodynamics, the determinants of coronary blood flow and myocardial oxygen demand, and the parameters of blood oxygen-transport function during alveolar mobilization in early periods after extracorporeal circulation in patients operated on for coronary heart disease. Subjects and methods. Twenty-nine patients were examined after myocardial revascularization. The alveolae were mobilized 63±2 min after extracorporeal circulation. The peak airway pressure was 31±0.3 H2O. Invasive hemodynamic monitoring was provided with Swan-Ganz catheters. Results. After building up the peak airway pressure, there was a 7.5—15 mm Hg blood pressure reduction (p<0.05) and 3.7 mm Hg right atrial and pulmonary artery wedge pressure elevations (p<0.05). Total pulmonary vascular resistance increased by 44% (p<0.05). Cardiac index reduced by 15% (p<0.05) due to decreased stroke volume. Coronary perfusion gradients and myocardial oxygen demand proportionally changed: r=0.62—0.77 (p<0.001). Oxygen transport significantly unchanged due to alveolar mobilization. After the latter, there was a close correlation between oxygen delivery and uptake (r=0.74; p<0.001). After alveolar mobilization, the changes in oxygen utilization coefficient and cardiac index had a significant correlation (r=0.43; p=0.02). After switching to artificial ventilation in the fitted mode, all the study parameters did not differ from the baseline values. Conclusion. The production of the peak airway pressure required for alveolar mobilization is attended by cardiac depression due to the right and left ventricular function determinant changes resulting in reductions in stroke volume and blood pressure. At the same time, there is imbalance between the conditions for coronary blood flow and the myocardial oxygen demand values. After artificial ventilation with the fitted positive end-expiratory pressure is switched, the mean hemodynamic values return to the baseline levels; however, there are signs of tense blood transport function. Key words: alveolar mobilization in cardiosurgical patients, hemodynamic effects of alveolar mobilization, recruitment maneuver.